Business ownership and self-employment in developing economies: the colombian case (2008)
We characterize entrepreneurship in developing economies through a case study for Colombia. We document self-employment and business ownership since the 1980s; while the relative size of these groups within the labor force is stable across time, they differ significantly in important observable dimensions such as education and business sector. We then study the motivations to become an entrepreneur. First, we analyze the transition into and out of potential forms of entrepreneurship by measuring the flows across occupations, and study the determinants of entry and exit into and out of self-employment and business ownership; there is surprisingly little transition between self-employment and business ownership. Second, we focus on the financial motivations by measuring the differences in earnings of self-employment and business ownership relative to salaried work, at the mean and along the distribution. There is a substantial earnings premium to become a business owner, but it is not financially attractive to become self-employed. The results of this paper suggest that while business ownership is what the literature associates with entrepreneurship, self-employment Is basically a subsistence activity.